Inflammatory consequences of divergent cell death signals - Kearney, Conor J. (Trinity College (Dublin, Ireland). Department of Genetics, 2015)
Tumor Necrosis Factor (TNF) is an apical cytokine that drives inflammation through triggering the synthesis and secretion of multiple downstream pro-inflammatory cytokines and chemokines. Generally, TNF stimulation does not result in cell death, however, under particular conditions, TNF can drive apoptosis or necroptosis. The Inhibitor of Apoptosis Proteins (IAPs) often dictate whether TNF stimulation results in cytokine secretion and cell survival, or alternatively, cell death. This occurs by facilitating NFKB activation through ubiquitination of RIPK1. Furthermore, TNF can induce a form of regulated necrosis, called necroptosis if caspase-8 activity is inhibited Necroptosis is also inhibited by IAPs and is thought to be initiated by RIPK1 and RIPK3. Indeed, necroptosis represents an alternative and unusual outcome of TNF stimulation, preventing normal TNF function in driving cytokine and chemokine production, but promoting release of Danger Associated Molecular Patterns (DAMPs).
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin